Proceedings of the 46th ACM Technical Symposium on Computer Science Education 2015
DOI: 10.1145/2676723.2677284
|View full text |Cite
|
Sign up to set email alerts
|

An Experience Report at Teaching a Group Based Agile Software Development Project Course

Abstract: Teaching group based Agile software development project courses is difficult. There are many aspects that need to be considered for a project to be successful such as a well defined scope, students working effectively together, and engaging with the customer. In this paper we present an experience report at teaching an Agile software development project course that involved teams developing web applications. The resources developed for the course and discussion about our experience will help inform others who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Anslow et al [1] reported their experience of teaching Agile methods to undergraduate and graduate students and presented a course outline along with associated teaching materials. They recommended not to teach the course to different levels simultaneously due to the nature of different levels of assessment required, abilities of the students, and additional administrative overheads.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Anslow et al [1] reported their experience of teaching Agile methods to undergraduate and graduate students and presented a course outline along with associated teaching materials. They recommended not to teach the course to different levels simultaneously due to the nature of different levels of assessment required, abilities of the students, and additional administrative overheads.…”
Section: Related Workmentioning
confidence: 99%
“…Each student must take 10 courses in any order over a four year period and are used as credit towards a Masters' degree (MSc) in Software Engineering awarded by the University of Oxford. In 2007 the Agile Methods (AGM) course 1 was introduced in response to the growing needs for software engineering professionals to understand and introduce Agile in their work places.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous recent articles focus on Agile practices in education, e.g., [15,10,17,2], which indicates the will and the need to teach students this methodology, especially in Computer Science and Information Technology. These articles show that the use of Agile methods in educational activities has very positive effects.…”
Section: Agile Methodology In Educationmentioning
confidence: 99%
“…The platform is made of EPP (expanded polyproylene), so there is no body harm if an uncontrolled drone accidentally crashes on a student or a teacher. Parrot also includes a software development kit (SDK) 2 and numerous open projects such as Paparazzi 3 or ROS 4 use this platform. The main skills used on this platform were related to software development, including real-time movie processing.…”
Section: Platformsmentioning
confidence: 99%
“…It is therefore important for students to learn and practice agile project development before they enter the software industry. Many educators shared their experiences in teaching agile methodologies 4,5,6,7 ; however, to the best of our knowledge, there is no prior work integrating risk as a driver for the students to evaluate and advance their team-based agile projects. This knowledge gap is significant because risk is fundamental to change 2,8 and it is part of the agile manifesto to value continuous and quick responses to change 3 .…”
Section: Introductionmentioning
confidence: 99%